Quality of maternal healthcare: Theoretical perspective on quality measurements - Rehman, Adeela; Mohamad Diah, Nurazzura (2016)
Background: Maternity care is an imperative aspect of healthcare systems due to its demand of intensive care focusing on mothers' and newborns' health. By consideration, child birth is a natural process but needs appropriate care. Provision of quality care to mothers and newborns at healthcare centers and hospitals is crucial for consideration in health systems. Method: The paper consisted of conceptual understanding of the measurement of quality care for maternal and newborns in hospitals. After careful screening of the available literature, 30 articles were selected and reviewed for this paper. Results: Various literature focused on three perspectives to study quality of care i.e; structure, process and outcome. Hospitals are the place to provide short term care service to the patient revolved around the activities provided by doctors, nurses and other staff. The utilization of efcient health services depends on the providers' ability and competence to deliver quality care, which shows the process of health services. On the other hand, the patient's centeredness is also the apex agenda to know the outcome of the services delivered to them. Conclusion: Therefore, in order to study quality of health care it is necessary to highlight the provision of quality care services in terms of structure, process and patient's perspective towards health care services and its quality to achieve better outcomes for maternity care.